The Influence of Religion-Based Social Entrepreneurship on Poverty Alleviation - Nikmah, Choirul; Nugraha, Jaka; Hung, Rern-Jay (Jurnal Pendidikan Ekonomi, 2025)
Social entrepreneurship is an idea of social change based on an entrepreneurial approach. The phenomenon of social entrepreneurship has proliferated along with efforts to resolve various social problems, such as economic improvement and poverty alleviation. This present study aims to describe the role of social entrepreneurship in the context of building a community economy that has an impact on poverty alleviation that focuses on social business. The social business entity that is the case study is the Nurul Hayat Foundation. Qualitative analysis is used in this study. From this research, social entrepreneurship plays a real and important role in solving social problems. Social value creation and innovation are the main instruments in social entrepreneurship. In addition, the Nurul Hayat Foundation has played a role in encouraging community economic improvement to alleviate poverty. This study indicates that social objectives with the impact of community empowerment become important values in the practice of social entrepreneurship. Keywords: Social entrepreneurship, poverty alleviation, social business